Atrial Septal Defect Closure Device Dislodgement - Emergency Surgical Retrieval - Rahman, Mostafizur; Hossain, Md. Aslam; Hasan, Md. Kamrul; Khan, Omar Sadeque; Shaha, Sanjoy Kumar; Adhikary, ASit Baran (Journal of Dhaka Medical College, 2013)
J Dhaka Medical College, Vol. 21, No. 2, October, 2012, Page 209-210 DOI: http://dx.doi.org/10.3329/jdmc.v21i2.15360